On the development of a neoantigen vaccine for the prevention of Lynch Syndrome. Issue 1 (25th March 2022) - Solomon, Adam; Alteber, Zoya; Bassan, David; Sharbi‐Yunger, Adi; Esbit, Simon; Tzehoval, Esther; Eisenbach, Lea
Abstract: Lynch Syndrome (LS) is an autosomal dominant genetic condition that causes a high risk of colorectal cancer. The hallmark of LS is genetic instability as a result of mismatch repair (MMR) deficiency, particularly in repetitive low complexity regions called microsatellites (MS). MLH1 −/− mice deficient in MMR are prone to developing tumors in the colon, upon oral administration of dextran sodium sulfate (DSS), at a rate of more than 70%. Using this LS mouse model, we found a novel tumor neo‐antigen from a deletion mutation of the coding MS in the SENP6 gene that prevented tumorigenesis or hindered tumor growth rate in immunized mice. This was accomplished via high throughput exome sequencing of DSS‐induced colorectal tumors in the MLH1 −/− mice and predicting the most highly immunogenic mutant gene products processed and presented as antigens in C57BL/6 MHC‐I molecules. Throughout our study, we were able to prove the validity of the vaccine by analyzing the colorectal tumors in immunized DSS‐treated mice using either our epitope, called Sp6D1, or an unrelated peptide as a negative control. Tumors developed in this context were found to be antigenic and Sp6D1‐specific CD8 + tumor infiltrating lymphocytes were detected by flow cytometry and cytotoxic T lymphocytes (CTL) killing assays. Additionally, immunohistochemistry showed that tumor‐adjacent tertiary lymphoid organs were a potentially significant source of CD8 + lymphocytes. Altogether, our results indicate that there may be a protective effect to patients carrying LS mutations through the induction of a peptide‐specific CTL response from the use of neoepitope vaccination. Abstract : What's new? The highly immunogenic nature of Lynch Syndrome (LS) and the increased presence of activated cytotoxic T lymphocytes in LS spectrum tumors suggest the possibility to induce a robust cytotoxic immune response before the tumor can escape immune surveillance. Here, the authors used tumor exome sequencing and antigen prediction to design a peptide vaccine. Prophylactic immunization with neoantigen‐loaded bone marrow‐derived dendritic cells in a LS mouse model resulted in decreased frequency and severity of colorectal tumors. The results indicate a potential protective effect of neoepitope vaccination in patients carrying LS mutations.